Gold nanoparticles:synthesis and application for halal authentication in meat and meat products - Subara, Deni; Jaswir, Irwandi (INSIGHT - Indonesian Society for Knowledge and Human Development, 2018)
The Muslim community has recently become more aware of the food they eat, especially Muslim minorities in secular areas. This awereness is increased along with increasing adulteration and substitution of expensive meat for cheaper material. Hence, meat authentication has become a major concern for both consumers and researchers alike. Many analytical methods for detecting Halal meat have been developed to address issues with meat authentication, such as HPLC, FTIR, GCMS and PCR. Nanotechnology has recently shown great potential in biosensing applications for Halal meat products. Rapid testing, cheaper materials and portability of gold nanoparticle-based sensors are expected to change conventional sensing of Halal meat. Selected molecules and types of meat was one of the target for developing gold nanoparticles in the detection. Detection of meat products using gold nanoparticles is based on the colour changed of its optical properties. This article reviewed the application of gold nanoparticles for Halal authentication of meat and meat products. Furthermore, the recent development in preparation of gold nanoparticles and current challenges are also discussed. Gold nanoparticles shows great potential to detect specific meats in meat products. Several traditional and modern meat processed products have been tested on the application of gold nanoparticles, such as meat ball and burgers. However, detection of meat adulteration on real food samples should be done before the comercialization. Limit of detection of gold nanoparticles in analysis shows an increment. Gold nanoparticles offer new alternative to expensive method. In adition, specific detector for different animal meats of interest need to be designed.